Capturing and assessing the chemical milling process capability - Sun, Yuhui (Cranfield University, 2011)
In order to support the chemical milling process decision making on the new product producing, a process capability model is developed. The model uses process factors, capability measures and the assessing methods to capture the present chemical milling process capability on the new products. The inputs for this model implementation include a set of common product and production information. This model covers a wide range of capability measures, which are recommended by the manufacturing engineers. Despite of traditional statistical capability indices such as Cp/Cpk, this research assesses the chemical milling process capability within the manufacturing system which consists of process, product and resource. The estimations about chemical milling process capacity and process efficiency are covered in the model’s implementation.
Keywords: Process Factors; Capability Measures; Capability Modelling; Chemical Milling Productivity; Aircraft Manufacturing